Feminism Confronts Homo Economicus : Gender, Law, and Society - Dougherty, Terence; Fineman, Martha (Book collections on Project MUSE., 2005)
"The essays in this volume confront the inroads that economics has made into the legal academy ... Law and Economics uses principles of neoclassical economics to develop laws and social policies that maintain if not bolster current allocations of power."--The IntroductionThe Law and Economics school has had a significant impact on the legal and governmental landscape in the United States. It posits a perfectly rational "economic man"-homo economicus-who is unconstrained by familial and communal ties and who can and should make decisions solely in light of considerations of economic value. Feminism Confronts Homo Economicus offers a major intervention in debates about how law has come under the influence of economic principles. Drawing on the latest thinking in the fields of feminist legal theory, critical legal studies, and feminist economics, the essays critique the notion that legal and policy decisions should be made solely through the lens of economics. While the contributors question the wholesale incorporation of the neoclassical economic model into legal analysis, they do not all discard economic analysis and theory. Situated at the intersection of feminism, law, and economics, Feminism Confronts Homo Economicus will appeal to scholars and students of these disciplines as well as policy analysts and social theorists interested in family, education, labor, and welfare